Enrichment of lithium in lettuce plants through agronomic biofortification - da Silva, Rubens Ribeiro; de Faria, Alvaro José Gomes; Alexandrino, Gilson do Carmo; Ribeiro, Evandro Alves; dos Santos, Antônio Carlos Martins; Deusdara, Tulio Teixeira; do Nascimento, Ildon Rodrigues; Nascimento, Vitor L. (Journal of plant nutrition, 2019)
Biofortification of crops with lithium (Li) is a new trend in agriculture and researches on this subject still scarce, therefore, this work aims to evaluate the accumulation potential and the effects in agronomic characteristics of lettuce (Lactuca sativa L.) submitted to foliar application of two Li chemical sources and different concentrations. The experiment was conducted in a greenhouse and the applications of lithium hydroxide (LiOH) and lithium sulfate (Li 2 SO 4 ) were done via foliar spray at concentrations ranging from 0 to 40 mg dm −3 . The applications were divided into three applications distributed at 15, 25, and 35 days after transplanting. Positive and promising results were observed in agronomic characteristics and Li in accumulation. High concentrations of Li (40 mg dm −3 ) may compromise the development of lettuce plants, however, lower concentrations applied (16 to 26 mg dm −3 of Li) promoted an increase in dry weight of roots and shoot/root ratio, both chemical forms, and stem diameter and specific leaf area, Li 2 SO 4 , suggesting beneficial effect of this element. Li accumulation in shoots depend on the concentrations of this element in the applied solution of Li but not on its chemical form.